2020
DOI: 10.7759/cureus.12230
|View full text |Cite
|
Sign up to set email alerts
|

Association of Antenatal Risk Score With Maternal and Neonatal Mortality and Morbidity

Abstract: Introduction/Objectives Women with high-risk pregnancies require careful follow-up, management, and efficient allocation of resources to achieve optimal pregnancy outcomes. This study investigated the association between an updated, validated antenatal risk index score and neonatal mortality and morbidity in a tertiary care center in Saudi Arabia. Methods This retrospective cohort study included pregnant women delivered at King Abdulaziz Medical City, Jeddah, Saudi Arabia, betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Maternal and neonatal complications were significantly increased in high-risk mothers, which suggested the use of a risk assessment method to prevent adverse pregnancy outcomes by early detection and treatment of HRP. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…Maternal and neonatal complications were significantly increased in high-risk mothers, which suggested the use of a risk assessment method to prevent adverse pregnancy outcomes by early detection and treatment of HRP. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that unplanned out-of-hospital birth may be associated with an increases perinatal mortality, due to limited accessibility to certain urgent medical interventions or inadequate antenatal care [ 41 43 ]. Finally, the duration of the mother’s stay in the hospital may have been associated with birth outcomes [ 44 ], but the data were not available in the analyses, and might be included in future research agenda.…”
Section: Discussionmentioning
confidence: 99%
“…Also, this study is conducted in a single center, which might not reflect the actual prevalence in Saudi Arabia. We recommend a national multi-center study with multidomain factor assessment, including socioeconomic and antenatal variables [ 35 , 36 ]. The follow-up should be comprehensive, considering particular risks such preterm infants have, like increased risk of respiratory diseases and health care utilization, especially during the COVID-19 pandemic [ 37 - 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The follow-up should be comprehensive, considering particular risks such preterm infants have, like increased risk of respiratory diseases and health care utilization, especially during the COVID-19 pandemic [ 37 - 39 ]. National guidelines should be developed based on country-specific resources and parents' values [ 36 ].…”
Section: Discussionmentioning
confidence: 99%